2007
DOI: 10.1074/jbc.m704789200
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Polyglutamine Protein Oligomers in Cells by Fluorescence Correlation Spectroscopy

Abstract: Abnormal aggregation of misfolded proteins and their deposition as inclusion bodies in the brain have been implicated as a common molecular pathogenesis of neurodegenerative diseases including Alzheimer, Parkinson, and the polyglutamine (poly(Q)) diseases, which are collectively called the conformational diseases. The poly(Q) diseases, including Huntington disease and various types of spinocerebellar ataxia, are caused by abnormal expansions of the poly(Q) stretch within diseasecausing proteins, which triggers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
76
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(87 citation statements)
references
References 50 publications
11
76
0
Order By: Relevance
“…3: C and D). Similar to our studies, other groups have demonstrated by different methods that Congo red inhibits oligomerization of mutant proteins with expanded polyglutamine using fluorescence resonance energy transfer and fluorescent correlation spectroscopy (28,39). These findings strengthen the hypothesis that improved mobility of mutant γPKC by Congo red is caused by inhibition of oligomerization.…”
Section: Discussionsupporting
confidence: 80%
“…3: C and D). Similar to our studies, other groups have demonstrated by different methods that Congo red inhibits oligomerization of mutant proteins with expanded polyglutamine using fluorescence resonance energy transfer and fluorescent correlation spectroscopy (28,39). These findings strengthen the hypothesis that improved mobility of mutant γPKC by Congo red is caused by inhibition of oligomerization.…”
Section: Discussionsupporting
confidence: 80%
“…Small oligomers have been implicated as the causal agents in many proteinopathies. To monitor changes in the population of Htt103Q oligomers caused by our PrD enhancers and suppressors in yeast, we used fluorescence correlation spectroscopy (FCS) (25). To concentrate our analysis on the Htt103Q protein that was not localized to large aggregates, cell lysates were subjected to centrifugation to remove them.…”
Section: Resultsmentioning
confidence: 99%
“…For polyQ-containing proteins, oligomers form before IBs, their formation is polyQ length-dependent, and their presence is well correlated with cell death (25,37). Both chaperones that remodel oligomers and peptides that inhibit oligomer formation suppress toxicity (38,39).…”
Section: Discussionmentioning
confidence: 99%
“…QBP1 decreased the amount of expanded polyQ protein oligomers, and the effect was greater for shorter length polyQ stretches [29,30] (Table 2). These results are consistent with our in vitro data, which show that QBP1 inhibits the monomeric conformational transition of the polyQ protein that occurs before oligomer and aggregate formation.…”
Section: Therapeutic Effects Of Qbp1 On Cell Culture Modelsmentioning
confidence: 99%